2019
DOI: 10.1002/jemt.23236
|View full text |Cite
|
Sign up to set email alerts
|

Effects of human umbilical cord mesenchymal stem cells on co‐cultured ovarian carcinoma cells

Abstract: Ovarian carcinoma is mainly treated by surgery aided by chemotherapy. If supplemented by stem cells treatment, its recurrence rate and mortality rate will be decreased. This is a new therapy. In this study, ovarian cancer cells were cultured together with umbilical cord mesenchymal stem cells (UCMSCs), and the interactions between them were observed. The results showed that the survival rates of UCMSCs increased to 83.8 ± 2.2% from 56.5 ± 5.5%, and the survival rates of ovarian cancer cells decreased to 16.2 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The mortality rates of ovarian cancer are increasing and no known therapy has proven efficacy in inhibiting or delaying the progression of the disease. Recently MSC has emerged as a potential therapeutic cell therapy for many diseases including some form of cancer [32, 33]. Many controversies have been reported concerning the use of MSCs in cancer, few reporting the inhibition of the tumor invasiveness and metastasis [34, 35] and others reporting an increase in tumorogenecity [36, 37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mortality rates of ovarian cancer are increasing and no known therapy has proven efficacy in inhibiting or delaying the progression of the disease. Recently MSC has emerged as a potential therapeutic cell therapy for many diseases including some form of cancer [32, 33]. Many controversies have been reported concerning the use of MSCs in cancer, few reporting the inhibition of the tumor invasiveness and metastasis [34, 35] and others reporting an increase in tumorogenecity [36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…For example, UCMSCs displayed the obvious inhibition effects on tumorous growth in the research of malignant tumors including, melanoma, colon carcinoma, hepatocarcinoma, mammary cancer, hematological malignancy and pulmonary carcinoma [3740] Xiufeng Li et al, showed that, with the prolonging of co-culture time of Caov-3 and hUCMSCs, the number of apoptotic CAOV3 cells became more and more; and their proliferation was inhibited remarkably where stem cell grew, ovarian cancer cells were enclosed first, then gradually necrosed and developed into clusters of granules [33]. This confirm that MSCs can alter the metastatic profile of ovarian cancer [33, 41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ding, Chang, Shyu, & Lin, ; S. Yin, Ji, Wu, Jin, & Qian, ). Numerous studies have explored the potential effects of hucMSCs in treatment of various diseases such as diabetes (Bi et al, ), cancer (Xiufeng Li & Li, ), and liver (Guo et al, ), bone (Day et al, ), cartilage (K.‐C. Wu, Chang, Liu, & Ding, ), brain (Tanaka et al, ), and cardiovascular (X. Li et al, ) disorders both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the synthesis of kinases, including AKT, phosphoinositide 3-kinase (PI3K), ERK, STAT3, and the mammalian target of rapamycin (mTOR), were significantly reduced in both tumor cell types when co-cultivated with MSCs [ 61 , 62 ]. Cord blood MSCs have also shown an inhibitory effect on ovarian cancer cells CAOV-3 in co-culture, where increases in the number of apoptotic CAOV-3 cells alongside decreased proliferation were noted [ 63 ].…”
Section: Antitumor Properties Of Mesenchymal Stromal Cellsmentioning
confidence: 99%